The Impact of Chatbots on the Relationship between Integrated Marketing Communication and Online Purchasing Behavior in The Frontier Market - Khoa, Bui Thanh (Universitas Semarang, 2021)
Artificial Intelligence (AI), applied in many fields, is the core of the fourth technological revolution. In business, AI is used for customer relationship management as applied in the autoresponder systems, i.e., chatbot. Chatbots were an essential tool in the marketing relationship as many companies applied this function to their website; hence, this study analyzed the influence of chatbots on the enterprise's integrated marketing communication (IMC) activities, resulting in impulse purchase behavior and repurchase intention behavior. The mixed research method was used, particularly the in-depth interview and the survey with 886 online consumers, who shop from the online websites with chatbots system in Vietnam as Tiki, Lazada, Sendo, excetera. The research results showed that the perceived usefulness and ease of use of chatbots have positively affected the attitude of online consumers to the IMC activities of businesses. Simultaneously, IMC leads to impulse buying as well as the repurchase intention behavior of customers. The study proposed some managerial implications for an online business to enhance the chatbot functions to consumer behaviors in the website.